2010
DOI: 10.1111/j.1751-7893.2010.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive study of pathways to care of high risk for psychosis adolescents in Korea

Abstract: Our findings showed that the Internet and family members were the key contacts in as many as 57% of high risk adolescents. In Korea, patients and caregivers both serve important roles in help seeking efforts. It is important for adolescents who are at high risk of psychosis in Korea to have easy access to information in recognizing mental health problems. Therefore, mass in-depth educating and public campaigning are important in recognizing the symptoms of early psychosis and in doing so can reduce the DUP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Fridgen et al, 2013;Rüsch et al, 2013;Von Reventlow et al, 2013). There have, however, been attempts to characterize pathways to (Schultze-Lutter et al, 2009;Shin et al, 2010;Cocchi et al, 2013;Stowkowy et al, 2013;Von Reventlow et al, 2013;Wiltink et al, 2013) and engagement with services in those who seek help (Green et al, 2011). However, only a minority of studies with relatively small sample sizes assessed symptoms or behaviours that initiated the contact (Addington et al, 2002;Stowkowy et al, 2013).…”
Section: Introductioǹmentioning
confidence: 94%
“…Fridgen et al, 2013;Rüsch et al, 2013;Von Reventlow et al, 2013). There have, however, been attempts to characterize pathways to (Schultze-Lutter et al, 2009;Shin et al, 2010;Cocchi et al, 2013;Stowkowy et al, 2013;Von Reventlow et al, 2013;Wiltink et al, 2013) and engagement with services in those who seek help (Green et al, 2011). However, only a minority of studies with relatively small sample sizes assessed symptoms or behaviours that initiated the contact (Addington et al, 2002;Stowkowy et al, 2013).…”
Section: Introductioǹmentioning
confidence: 94%
“…As the preferred mental HL source they had used in the past, children indicated television (61%), whereas parents referred to articles in magazines (63%); both children and parents mentioned information at the family doctor's office (61% and 62%, respectively). Another study revealed that the majority of respondents sought help through internet, family members or school personnel (57%) (Shin et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the HS people had neither explicit expectations of the type of help they would need (Brummitt & Addington, ) nor a clear understanding about their risk state (Boydell et al, ). There are early detection and intervention services for psychosis existing all over the world which provide access to help (Brimblecombe et al, ; Caplan et al, ; Cocchi et al, ; Cotton et al, ; Green, McGuire, Ashworth, & Valmaggia, ; Joa, Gisselgard, Bronnick, McGlashan, & Johannessen, ; Kotlicka‐Antczak, Pawelczyk, Rabe‐Jablonska, & Pawelczyk, ; Leopold, Pfeiffer, Correll, Bauer, & Pfennig, ; Lynch et al, ; McFarlane et al, ; Quijada, Tizon, Artigue, & Parra, ; Schultze‐Lutter, Picker, Ruhrmann, & Klosterkötter, ; Shin et al, ; Simon, Theodoridou, Schimmelmann, Schneider, & Conus, ), but our findings suggest that there seems to be a clear need of awareness campaigns to ameliorate the knowledge about psychosis and promote early help‐seeking. Findings suggest that knowledge, beliefs and attitudes about mental health care, experiences with mental illness and the parent‐child relationship are key factors in the understanding and utilization of HI (Boydell et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consonant with the collectivist cultural view of the family as the primary unit of decision making in society, the Mental Health Law in Korea specifically assigns responsibility to the family to access mental health care for an ill person (Ministry of Health Welfare and Family Affairs 2009). As might be expected, a recent study in Korea on pathways to mental health care for adolescents at risk for psychosis found the majority of intial contacts with mental health services were initated by the family (Shin et al 2010). Along with concerns over a rising rate of suicide (Ben Park and Lester 2006) and the nacent development of voluntary and outpatient mental health services in Korea, the cultural context of familial responsibility for ill family members may assist in understanding the high proportion of involunatry to total psychiatric hospitalizations reported by the WHO (World Health Organization and Ministry of Health and Welfare 2007).…”
Section: Introductionmentioning
confidence: 88%